The relationship between marital satisfaction and self-esteem among the lectures in a higher educational institute in Sarawak - Tan, Qiang Foon (Universiti Malaysia Sarawak (UNIMAS), 2009)
This research was aimed to identifY the level and relation between marital satisfaction and the level of self-esteem among the lecturers in one higher educational institute in Sarawak and also to identifY the differences in marital satisfaction between demography factors (gender, educational background and marriage duration). Research samples were 80 lecturers chosen randomly from six faculties in the institute. The level of marital satisfaction (task accomplishment, role performance, communication, affective expression, involvement, control and values and norms) was measured by Dyadic Relationship Scale with 42 items while the level of selfesteem was measured by Rosenberg Self-Esteem Scale with 10 items. The reliability coefficient for Dyadic Relationship Scale is 0.87 and for Rosenberg Self-Esteem Scale is 0.75. The collected data was analyzed into descriptive statistic and inference statistics at the significant level 0.05 (t-test and One-way ANOV A) and at the significant level 0.01 (Pearson Correlation) using Statistical Packages for Social Sciences Version 11.5. The result indicated that the level of marital satisfaction of lecturers were high in the aspects of task accomplishment, role performance, communication, affective expression, involvement, control, values and norms and in overall. The self-esteem was at the high level. The result indicated no significant difference in marital satisfaction between gender factor in the aspects of task accomplishment, role performance, communication, affective expression, control, values and norms and in overall but there exists significant difference in the aspect of involvement. The analysis also indicated no significant difference in marital satisfaction between educational background factor in overall including all aspects. The result indicated no significant difference in marital satisfaction between marriage duration factor in the aspects of task accomplishment, role performance, communication, involvement, control, values and norms and in overall but there exists significant difference in the aspect of affective expression. The result indicated an existence of a positive relation between the level of self-esteem and the marital satisfaction in overall including all aspects.